Competências de enfermagem forense: avaliação do conhecimento de enfermeiros - Souza, Jhuliano Silva Ramos De (2025)
Forensic Nursing is a specialty that integrates forensic clinical practice, offering support to victims, aggressors and their families in situations of violence. Recognized by the Federal Nursing Council, this area covers skills that range from identifying and managing cases of violence to collaborating in judicial expertise. Its areas of activity include sexual violence, the prison system, mental health, collection and preservation of traces, technical assistance, mass disasters, catastrophes and mistreatment throughout the life cycle. However, Forensic Nursing is still little explored in training curricula, resulting in knowledge gaps that affect professionals' practice. This study aimed to evaluate the knowledge of Primary Health Care Nurses about Forensic Nursing, before and after an online training based on the Competency Matrix of the Federal Nursing Council. Quasi-experimental study with pre- and post-test evaluation, involving 12 Primary Health Care Nurses in the South of Minas Gerais. Taking place between May and August 2023, based on the Problematization Methodology, online, with 60 hours, 20 asynchronous and 40 synchronous. The course was structured into five modules according to the eight areas of Forensic Nursing. A questionnaire, developed and validated by the authors, was used, which included sociodemographic data and specialty skills. The research was conducted in three stages: 1) diagnostic assessment of knowledge as a pre-test; 2) training extension course and 3) post-intervention evaluation. Descriptive and inferential statistical analyzes and Fisher's Exact Test were performed for associations of independent variables of sociodemographic and work data and dependent variables of knowledge categories. The project was approved by the Research Ethics Committee of the Federal University of Alfenas under Opinion: 5.880.372/2023, CAAE: 65613222.9.0000.5142. The results identified an improvement in knowledge about the seven categories of the specialty. . In Competency A, greater familiarity with physical, psychological and/or emotional, sexual and domestic violence was observed; in Competency B, limitations in knowledge about medical-legal and criminal procedures were identified; in Competency C, there was a strengthening in the understanding of laws, such as the Child and Adolescent Statute and the Maria da Penha Law; in Competencies D and E, they revealed improvement in the identification of ethical practices and mental disorders related to violence in the prison system; in competencies F and G there was an improvement in knowledge about mass disasters and interpersonal relationships, with an impact on humanized care and emotional support for victims and families. Participants rated the course as excellent in terms of structure, organization, methodology, teaching program, technical material and facilitators. The training was seen as effective in improving knowledge about violence and management of victims, aggressors and family members, strengthening the interface between health and justice. Despite not having reached significance for all correlations, the course added knowledge for professional practice. Low adherence to the online course indicates the need for strategies to increase participation and validate results with larger samples.